Organizational systems, commercialization and cost benefit analysis of Indian space programme - K. R. Sridhara Murthi, U. Sankar and H. N. Madhusudhan (CURRENT SCIENCE, VOL. 93, NO. 12, 25 DECEMBER 2007, 2007)
During the last four decades, ISRO has developed capabilities and infra-technologies in broadcasting, communications, meteorology, remote sensing and space scienceresearch and has made significant contributions to several areas of national development. The organizational systems of ISRO have been designed to ensuremaximum autonomy, creative and innovative environment that are conducive for a performance-oriented system, besides developing unique institutional mechanismsfor participation of industry, academia and user agencies. Project/mission mode of working has been a hallmark of ISRO. The satellites and launch vehicles of ISROhave been cost effective and the benefits derived from the space programme have exceeded the costs. Commercialization of India's space capabilities receivedimpetus through Antrix Corporation, which has set a new model by adopting a very lean and efficient structure for marketing of space products and services. This article discusses the unique organizational feature of ISRO, the salient aspects of commercialization and cost-benefit aspects of India's space programme.